A Study on Level of Awareness About Agricultural Commodity Derivatives Among Farmers in Karnataka - Babshetti, Vaijanath; Basanna, Prakash (Indian Journal of Research in Capital Markets, 2016)
Financial derivatives have attracted the attention of scholars and academicians. As a result, various studies have been carried out with respect to price discovery, liquidity, and investor awareness. However, there is still an absence of substantial research in the area of Indian commodity derivatives. Hence, we undertook the problem of lack of awareness of agricultural commodity derivatives among farmers for the current study. The level of awareness about agricultural commodity derivatives among farmers was assessed by administering a questionnaire to 460 farmers randomly selected across the state of Karnataka. Several studies have shown that the participation of farmers in agricultural derivatives has been very negligible. The lack of higher level of education among farmers, prevalence of excessive speculation, and lower liquidity are some of the reasons for non involvement of farmers in commodity derivatives. Despite commodity derivatives having been present for many years, their benefit has not reached the farming community. If the government undertakes necessary steps based on the suggestions/recommendations given by the researchers/committees, the awareness of farmers about agri commodity derivatives can be improved.